Magnetism in graphene oxide induced by epoxy groups - Lee, Dongwook (2015)
We have engineered magnetism in graphene oxide. Our approach transforms graphene into a magnetic insulator while maintaining graphene's structure. Fourier transform infrared spectroscopy spectra reveal that graphene oxide has various chemical groups (including epoxy, ketone, hydroxyl, and C-O groups) on its surface. Destroying the epoxy group with heat treatment or chemical treatment diminishes magnetism in the material. Local density approximation calculation results well reproduce the magnetic moments obtained from experiments, and these results indicate that the unpaired spin induced by the presence of epoxy groups is the origin of the magnetism. The calculation results also explain the magnetic properties, which are generated by the interaction between separated magnetic regions and domains. Our results demonstrate tunable magnetism in graphene oxide based on controlling the epoxy group with heat or chemical treatment.